2022
DOI: 10.1038/s42003-022-03753-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling SARS-CoV-2 and influenza infections and antiviral treatments in human lung epithelial tissue equivalents

Abstract: There is a critical need for physiologically relevant, robust, and ready-to-use in vitro cellular assay platforms to rapidly model the infectivity of emerging viruses and develop new antiviral treatments. Here we describe the cellular complexity of human alveolar and tracheobronchial air liquid interface (ALI) tissue models during SARS-CoV-2 and influenza A virus (IAV) infections. Our results showed that both SARS-CoV-2 and IAV effectively infect these ALI tissues, with SARS-CoV-2 exhibiting a slower replicati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 120 publications
1
15
0
Order By: Relevance
“…It has also been shown that addition or enhancement of ECM deposition in neural 2D co-cultures accelerated the formation of neural networks, and in one example, the drug responses were more similar to those obtained in vivo 11 , 12 , thus reproducing evidence from in vivo experiments that ECM plays an important role in the development and function of the neural circuitry in the brain. Similar data has now also been shown for many non-neuronal 3D tissue models 13 15 .…”
Section: Introductionsupporting
confidence: 83%
“…It has also been shown that addition or enhancement of ECM deposition in neural 2D co-cultures accelerated the formation of neural networks, and in one example, the drug responses were more similar to those obtained in vivo 11 , 12 , thus reproducing evidence from in vivo experiments that ECM plays an important role in the development and function of the neural circuitry in the brain. Similar data has now also been shown for many non-neuronal 3D tissue models 13 15 .…”
Section: Introductionsupporting
confidence: 83%
“…However, animal models are expensive, rarely accurately mimic human biological responses due to obvious differences in physiology, pathology and other genetic factors, as well as having ethical issues. Air-liquid interface (ALI)-culture airway epithelium are being increasingly recognized for their ability to overcome many of the disadvantages of submerged cell culture models ( 1 3 ). They consist of pseudostratified fully differentiated cells, cultured in transwell inserts, wherein the apical cells are exposed to the air and the basolateral cells fed by culture medium from below, and thus are a more structurally and biologically accurate representation of the human respiratory microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Using Vero TA6 cells, a Vero E6-derived monkey epithelial cell line overexpressing human TMPRSS2 and ACE2, we found that PIXN effectively mitigated the entry of an authentic SARS-CoV-2 variant (USA-WA1/2020) (Figure 1D), which depends mainly on endocytosis (Figure S1C) 11,22 . Furthermore, in a 3D-EpiAirway system simulating human airway infection (Figure 1E) 32 , PIXN-treated samples at both 24 and 96 hours post SARS-CoV-2 infection showed a dose-dependent reduction in viral load when compared to vehicle-treated controls (Figure 1F). Meanwhile, measuring the released lactate dehydrogenase (LDH) in the medium as an indicator of cytotoxicity detected no signi cant cell death in PIXN-treated samples except in prolonged treatment with the highest dose (20 µM) (Figure 1G).…”
Section: Resultsmentioning
confidence: 99%